2003
DOI: 10.1046/j.1460-9592.2003.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new combined SpO2/PtcCO2 sensor in anaesthetized paediatric patients

Abstract: In anaesthetized children, the TOSCA ear sensor allows estimation of SaO2 and PaCO2, comparable in accuracy to endtidal capnometry and finger pulse oximetry. This makes the TOSCA monitor a helpful add-on to respiratory monitoring in anaesthetized children, in situations, in which endtidal capnometry is unreliable or difficult to establish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…Rohling and coworkers [25] reported excellent agreement of transcutaneously measured SpO 2 using the TOSCA device and SaO 2 in anaesthetized adult patients. Similar results were found in anaesthetized pediatric patients by Dullenkopf and co-workers [26] with a mean bias and limits of agreement of -0.63% and -3.4 / +2.1% respectively. In patients assessed for longterm oxygen therapy, Schafroth Török and colleagues [20] recently confirmed these results using a previous version of the V-Sign TM 2 sensor.…”
Section: Discussionsupporting
confidence: 87%
“…Rohling and coworkers [25] reported excellent agreement of transcutaneously measured SpO 2 using the TOSCA device and SaO 2 in anaesthetized adult patients. Similar results were found in anaesthetized pediatric patients by Dullenkopf and co-workers [26] with a mean bias and limits of agreement of -0.63% and -3.4 / +2.1% respectively. In patients assessed for longterm oxygen therapy, Schafroth Török and colleagues [20] recently confirmed these results using a previous version of the V-Sign TM 2 sensor.…”
Section: Discussionsupporting
confidence: 87%
“…Rohling and Biro [15] investigated the Kontron device (Kontron Monitor 7840 Kontron Instruments Medical Sensors, Basel, Switzerland) in anaesthetized adult patients and found good agreement between PtcCO 2 and PaCO 2 (mean bias )0.08 kPa; limits of agreement )0.38/ +0.22 kPa), and SpO 2 values differed less than 1% from those obtained by standard pulse oximetry. Dullenkopf et al [10] and Bernet-Buettiker et al [9] validated the TOSCA system (Linde Medical Sensors, Basel, Switzerland) in children and neonates, respectively. Both authors reported a good agreement between PtcCO 2 and PaCO 2 , although their reported bias values differed significantly ()0.04 and +0.44, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, sensor preparation, positioning, taping, and the necessity for repeated changes of the sensorÕs location made handling difficult and complicated its use [9]. More recently, two new devices, the SenTec Digital Monitor V-sign sensor and the TOSCA devise, for combined assessment of PtcCO 2 and SpO 2 using a single ear-clip sensor were introduced [9][10][11][12]. To the best of our knowledge, only three studies assessing the accuracy and reliability of the V-Sign sensor (V-Sign Sensor, SenTec Digital Monitoring System: SenTec AG, Therwil, Switzerland) have so far been published: one in adult volunteers [11], one in patients during bronchoscopy [12], and one in critically ill patients in a medical intensive care unit (ICU) [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturer, the sensor has to be changed between the left and the right ear lobe only twice a day, because the skin is warmed only to 42°C as opposed to 44°C in other sensors and only low pressure is applied to the ear lobe. Technical details and function are described in detail by Eberhard et al 4 and Dullenkopf et al 5 The sensor was modified in cooperation with the manufacturer for its use on the thin ear lobe of neonates with a Varihesive layer (Conva Tec, Princeton, NJ) on the reflecting side (Fig 1). This modification was necessary to compensate for the gap of 3 mm between the flanges of the clip, which was too large for the thin ear lobes of neonates.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 So far, no data are available about suitability and reliability of the monitor in newborn infants. Thus, the aim of the present study was to evaluate the performance and reliability of the Spo 2 and Ptcco 2 reading of this monitor in newborns.…”
mentioning
confidence: 99%